Definition of the Term «Pedagogical Technology» in the Context of Forming Modern Paradigm in Education - Iryna Tamozhska (Pedagogical Discourse, 2015)
In the article the advantages of a technological approach in a system of future experts training are proved. There is a definition of a phenomenon and the concept «pedagogical technology». Scientists’ various approaches to this concept understanding are generalized. It is noticed that «the pedagogical technology» is considered by scientists as well as means and communication process, and as accurately organized pedagogical system with a set of methodological tools. Requirements imposed by scientists to the pedagogical technology are noted, namely: scientific and pedagogical availability and its conceptual interpretation by the teacher taking into consideration conditions of the real educational process presented by various pedagogical situations; providing continuous development of personality in educational space in the process of interaction with a teacher; reservation of educational space authorship and creativity by each teacher; correlation to real teaching and educational process.